Buku Ajar Bahasa Jawa Piwulang Keluarga untuk Meningkatkan Efektivitas Pembelajaran di Madrasah Ibtidaiyah - RULI ASTUTI; Lailatul Maghfiroh (IAI Al Khoziny Buduran Sidoarjo, 2021)
This study aims to develop Javanese textbook Piwulang Keluarga to improve the effectiveness of Javanese learning for grade 2 students at MI Al Muawanah Sidoarjo. The method used in this research is Research and Development (R&D) using the Walter Dick and Lou Carey development model. The instruments used to collect the data are test and questionnaires. The textbook produced in this study has valid criteria, it can be seen from the results of validation of content expert, design expert, and linguist respectively getting percentage of 90%, 80% and 80%. The results of the t test analysis with a significance level of 0.05 showed that the statistical p-value of the t test was 0.026 which means (<0.05). It means that there is a significant effect on the average pretest and posttest scores. The implementation of Javanese Piwulang Keluarga textbook at grade 2 MI Al Muawanah is able to increase the effectiveness of Javanese learning, it is proven by the score of students’ learning outcomes almost entirely above the minimum completeness criteria. In addition, the implementation of this textbook makes students can think critically, be able to solve problems in everyday life, and students’ learning outcomes have increased.